Joining of trinuclear (CuL)2M (M = MnII and CdII) nodes by 1, 3- and 1, 4-benzenedicarboxylate linkers: positional isomeric effect on co-crystallization. Issue 41 (28th September 2018) - Dutta, Sabarni; Jana, Subrata; Mahapatra, Prithwish; Bauzá, Antonio; Frontera, Antonio; Ghosh, Ashutosh
Abstract : Among the four one-dimensional coordination polymers obtained by joining (CuL)2 M (M = Mn II and Cd II ) nodes with 1, 3- and 1, 4-benzenedicarboxylate linkers, the chains derived from 1, 3-benzenedicarboxylate are co-crystallized with dimeric Cu II units. Abstract : Four new one-dimensional coordination polymers {[(CuL)2 Cd( p -BDC)]·H2 O} n (1 ), {[(CuL)2 Mn( p -BDC)]·H2 O} n (2 ), {[(CuL)2 Cd( m -BDC)][(CuL)2 ]} n (3 ), and {[(CuL)2 Mn( m -BDC)][(CuL)2 ]} n (4 ), where H2 L = N, N ′-bis( α -methylsalicylidene)-1, 3-propanediamine, have been synthesized using bimetallic trinuclear nodes, [(CuL)2 M] (where M is Mn II /Cd II and p -BDC and m -BDC are 1, 4- and 1, 3-benzenedicarboxylate, respectively). Crystal structures show that all four complexes form 1D chains in which the heterometallic linear trinuclear nodes are connected by syn – syn bridging dicarboxylate linkers. However, in1 and2 the nodes which are connected by linear p -BDC are parallel to each other whereas in3 and4 the nodes are inclined towards each other to be connected by the angular m -BDC linker. Moreover, complexes3 and4 are co-crystallized with dimeric Cu II units which are accommodated in the cavities between polymeric chains. This difference in the solid-state crystal packing is explained theoretically by DFT calculations of complexes1 and3 considering the positional isomeric effect of dicarboxylate linkers. Variable temperature magnetic susceptibility measurements of complexes2 and4 indicate antiferromagnetic interactions between the Cu II and Mn II centers with J = −13.08 and −12.11 cm −1 for2 and4, respectively.